Strategi Pemerintah Desa Gandukepuh Terhadap Pengembangan Objek Wisata Religi: Gandukepuh Village Government's Strategy Towards The Development Of Religious Tourism Objects - Mukhirto, Mukhirto; Dwijayanto, Arik; Fathoni, Tamrin (Journal of Community Development and Disaster Management, 2022)
The purpose of the study was to explore the strategy for developing religious tourism objects and attractions at the tomb of Kyai Ageng Imam Musakaf, the required resources, supporting and supporting factors and analysis of strategies for developing religious tourism objects at the tomb of Kyai Ageng Imam Musakaf. This type of research is qualitative research, namely the research procedure produces descriptive data in the form of written or spoken words from people and observable behavior to understand the phenomena experienced by the research subjects. The results of the research are the development of religious tourism at the Kyai Imam Musakaf Tomb by managing tourist attraction objects (ODTW) using a management system. Natural resources include good and efficient management of places, facilities and infrastructure. Nice, clean and attractive environment. Supporting factors are the increasing number of pilgrims, enthusiastic residents, natural resources, and the role of caretakers. The inhibiting factors for promotion are limited, lack of cooperation and narrow road access. In carrying out the development of ODTW also requires supervision. Tujuan penelitian untuk menggali Strategi Pengembangan obyek dan daya tarik wisata religi di makam kyai Ageng Imam Musakaf, sumber daya yang diperlukan, faktor pendukung dan penghambat dan analisis strategi pengembangan objek wisata religi di makam kyai Ageng Imam Musakaf. Jenis penelitian ini adalah penelitian kualitatif, yaitu prosedur penelitian menghasilkan data deskriptif berupa kata-kata tertulis atau lisan dari orang-orang dan perilaku yang dapat diamati untuk memahami fenomena tentang apa yang dialami oleh subjek penelitian. Hasil penelitian yaitu pengembangan wisata religi di Makam Kyai Imam Musakaf dengan melakukan pengelolaan objek daya tarik wisata (ODTW) dengan menggunakan sistem manajemen. Sumber daya alam meliputi pengelolaan tempat, sarana, prasarana yang baik dan efisien. Lingkungan yang baik, bersih, dan menarik. Faktor pendukung yaitu bertambah banyaknya yang melakukan ziarah, Antusias warga, Sumber daya alam, dan peran juru kunci. Faktor penghambat yaitu Promosi terbatas, kurangnya kerjasama dan akses jalan sempit..